Analysis of the Cause of Titanium Endoprosthesis Failure - Hanusová, Patrícia; Palček, Peter; Uhríčik, Milan (Manufacturing Technology Journal, 2019)
This paper deals with the causes of failure of total hip replacement. Hip joint replacement is one of the most frequently used surgical procedures worldwide. More than 200,000 surgeries are performed only in Europe each year, following early attempts by John Charnley. Currently, more than 340 of the total 4431 implants per year are reoperated in Slovakia. Despite the excellent properties of the titanium alloy, endoprosthesis often fails and the hip replacement is necessary. Common causes are overloading and cracking, static or dynamic. Other causes of failure include injury, implantation failure, manufacturing inaccuracies, and non-compliance with the manufacturing process.
Keywords: endoprosthesis; fatigue; titanium alloy; hip joint